Holderlin's hymn "Remembrance" - Heidegger, Martin, 1889-1976 (Book collections on Project MUSE., 2018)
Martin Heidegger's 1941'1942 lecture course on Friedrich HOlderlin's hymn, "Remembrance," delivered immediately following his confrontation with Nietzsche, lays out a detailed plan for the interpretation of HOlderlin's poetry in which remembrance is a central concern. With its emphasis on the "free use of the national" and the "holy of the fatherland," the course marks an important progression in Heidegger's political thought. In addition to its startlingly innovative analyses of greeting, the festive, and the dream, the text provides Heidegger's fullest elaboration of the structure of commemorative thinking in relationship to time and the possibility of an "other beginning." This English translation by William McNeill and Julia Ireland completes the series of Heidegger's major lecture courses on HOlderlin.